Implementation of mobile IP on NTU campus network : a case study - Low, Boon Tuan (2008)
This case study considers the problem of providing network access to hosts whose physical location changes with time. The issues with host mobility using the existing Internet Protocol can be resolved with deployment of Mobile IP.